Do Options Exist ? : The Reform of Pension and Health Care Systems in Latin America. - Cruz-Saco, Maria Amparo (Pitt Latin American series., 1999)
This timely volume brings together specialists on the reform of social security systems to analyze the similarities and differences of those health care and pension reforms that have taken place since the early 1990s and suggests possible gains through recent or contemplated revisions to those systems.